Beneficial Use of White and Indian Mustard Seed Meals to Enhance Plant Growth and Nutrient Uptake. Issue 1 (7th February 2019) - Lewis, Katie L.; Hons, Frank M.; Gentry, Terry J.
Abstract : Core Ideas: Mustard seed meals (SM) added to soil >56 days before planting cotton and sorghum reduced negative growth effects. Mineral concentrations of cotton and sorghum were generally greater with SM and inorganic fertilizer treatments than the control. Before use as an organic fertilizer, the source, rate, and timing of SM applications should be considered. Oilseed crops have been widely evaluated for potential biodiesel production; however, for biodiesel to be economically and environmentally sustainable, feasible, and profitable means of by‐product (i.e., seed meal, SM) usage must also be developed. Utilization of SMs as a soil amendment in organic agricultural production systems offers one possible solution. This glasshouse study was conducted to determine the effects of mustard SMs (white mustard, Sinapis alba L., and Indian mustard, Brassica juncea L.) on aboveground growth and nutrient uptake by cotton ( Gossypium hirsutum L.) and forage sorghum [ Sorghum bicolor (L.) Moench] compared to inorganic fertilizer. The soil used was a loamy fine sand with low plant‐available N, P, and K. Seed meals were applied to soil at 1.0 and 2.5% by weight of soil. Compositional analysis of SMs used in this experiment indicated that the materials should contain sufficient nutrients to support plant growth; however, glucosinolates contained in these materials can also inhibit plant growth. A SM incubation period of 56 d reduced negative crop growth effects and should result in increased nutrient availability. For each measured nutrient parameter of cotton and sorghum, SM and inorganic fertilizer treatments generally resulted in values greater than the control. Dry matter N concentrations of two harvests of each plant species were greatest with 2.5% SM, followed by 1.0% SM and fertilizer. Seed meal applications may enhance nutrient availability and plant uptake and growth; however, the source, rate, and timing of SM applications should be considered before use as an organic fertilizer.